Advertising Appeals and Customer Loyalty in Telecommunication Firms in Portharcourt - Kenneth, C. Adiele; Wami, Solomon (Archives of Business Research, 2021)
The purpose of this study was to examine the relationship between Advertising Appeals and Customer Loyalty in Telecommunication firms in Port Harcourt. The study population comprised four (4) registered and functional Telecommunication service providing firms operating in Port Harcourt, Rivers State. The authors adopted a census study due to the small nature of the study population hence; there was no need for sampling. Thirty two (32) strategic managers of the four telecommunication firms constituted our respondents for the study. However, eight (8) respondents were randomly drawn from each of the telecommunication companies and thirty two (32) copies of structured questionnaire were administered to the managerial staff of the firms at their respective offices while twenty five (25) copies were retrieved, cleaned and used for the study. Descriptively, measures of central tendencies and measures of dispersions were used in analyzing the respondent’s demographics. Similarly, the Pearson Product Moment Correlation was used in testing the various hypotheses in other to ascertain the relationship between the predictor variable (Advertising Appeals) and the criterion variable (Customer Loyalty). The result of the analysis revealed that Advertising Appeals significantly influenced Customer Loyalty in Telecommunication firms in Port Harcourt. The study further discovered that amongst the dimensions of Advertising Appeals used in this study that Rational advertising appeal was found to be the most significant predictor of Customer Loyalty in Telecommunication firms in Port Harcourt. Hence, the researcher concluded that Advertising Appeals significantly affect Customer Loyalty and therefore recommended that the management of Telecommunication firms in Port-Harcourt should adopt the dimensions of advertising appeal used for the study as strategies for improving their level of customer loyalty.